Reconstructing Kyai Leadership in Strengthening the Quality of Islamic Boarding Schools Amid Digital Disruption - Imam Subhi; Deni Priansyah; Nova Tri Evriani; Rahman Rahman (JUMPA : Jurnal Manajemen Pendidikan, 2025)
The rapid advancement of digital technology has significantly transformed educational systems, including traditional Islamic institutions such as pesantren. This study aims to analyze the reconstruction of kyai leadership in strengthening the quality of pesantren in the era of digital disruption. A qualitative approach was employed using a Systematic Literature Review (SLR) method, drawing on relevant scholarly sources published within the last decade. Data were analyzed using thematic and content analysis to identify key patterns, challenges, and leadership transformations within the pesantren context. The findings reveal that kyai leadership is shifting from a predominantly centralized and traditional model toward a more adaptive and integrative approach. Major challenges include limited digital infrastructure and low levels of digital literacy among educators and students. At the same time, kyai are increasingly assuming roles as agents of transformation who promote technology-based educational innovation. This study proposes a conceptual model of Digital Kyai Leadership, integrating spiritual, transformational, digital, and collaborative dimensions as a strategic framework for enhancing pesantren quality. The findings underscore the importance of value-based and adaptive leadership in bridging Islamic traditions with contemporary educational demands. This study contributes to the development of Islamic education management and provides practical insights for strengthening pesantren leadership in the digital era.